(untitled) (Revista Latino-Americana de Enfermagem, 2023)
Objective: the objective of this study is to examine the relationship between the musculoskeletal problems experienced by the family members who care for stroke patients, physical health and disability levels. Method: the subjects included in the study were patients and family caregivers admitted to the Kanuni Sultan Suleyman Training and Research Hospital Physical Medicine and Rehabilitation outpatient clinic with a stroke diagnosis between May 30 th, 2019, and May 30 th, 2021. The caregivers were assessed using the Extended Nordic Musculoskeletal Questionnaire. Validated scales were employed to evaluate stroke patients’ physical health and disability level. Results: a total of 104 stroke patients and 104 caregivers who met our inclusion criteria took part in this study. Low back complaints in the last month were associated with the patients’ Functional Ambulation Score (FAS), Functional Independence Measure (FIM), Stroke Impact Scale (SIS) and Brunnstrom scores. Neck pain was the second musculoskeletal complaint, but was not statistically associated with patient-related factors. Upper limb problems were associated with FAS, FIM, SIS, Brunnstrom and the Modified Ashworth Scale scores. Conclusion: according to our findings, the low back is the body area most affected by musculoskeletal complaints in family caregivers of stroke patients, closely related to the patients’ functional capacity and disability levels. Clinical trials number: NCT04901637.